On Existence and Uniqueness of Common Fixed Point in C*-Algebra Valued Metric Spaces - Kumar, Deepak; Rishi Dhariwal (Science & Technology Asia, 2022)
In the present article, we prove some common fixed point theorems for two pairs of weakly compatible mappings satisfying rational type contractive condition in the framework of C*-algebra valued metric spaces. The proved results extend and generalize some of the results in the literature.